Terpenoid Biosynthesis Dominates among Secondary Metabolite Clusters in Mucoromycotina Genomes - Grzegorz Koczyk; Julia Pawłowska; Anna Muszewska (Journal of Fungi, 2021)
Early-diverging fungi harbour unprecedented diversity in terms of living forms, biological traits and genome architecture. Before the sequencing era, non-Dikarya fungi were considered unable to produce secondary metabolites (SM); however, this perspective is changing. The main classes of secondary metabolites in fungi include polyketides, nonribosomal peptides, terpenoids and siderophores that serve different biological roles, including iron chelation and plant growth promotion. The same classes of SM are reported for representatives of early-diverging fungal lineages. Encouraged by the advancement in the field, we carried out a systematic survey of SM in Mucoromycotina and corroborated the presence of various SM clusters (SMCs) within the phylum. Among the core findings, considerable representation of terpene and nonribosomal peptide synthetase (NRPS)-like candidate SMCs was found. Terpene clusters with diverse domain composition and potentially highly variable products dominated the landscape of candidate SMCs. A uniform low-copy distribution of siderophore clusters was observed among most assemblies. Mortierellomycotina are highlighted as the most potent SMC producers among the Mucoromycota and as a source of novel peptide products. SMC identification is dependent on gene model quality and can be successfully performed on a batch scale with genomes of different quality and completeness.